Synthesis and characterization of graphene using liquid phase exfoliation - Nur Ainina, Muhamad (2016)
Graphene is a two-dimensional single-layer sheet of sp2 hybridized carbon atoms has attracted tremendous attention and research interest, owing to its exceptional physical properties, such as high electronic conductivity, good thermal stability, and excellent mechanical strength. There are two categories of method that used in producing graphene which are bottom-up and top-down. In this study, graphene was synthesized using liquid phase exfoliation technique. The exfoliated graphene is synthesized from activated carbon, glycine and dimethylformamide (DMF). The functional groups of the sample was confirmed by Fourier transform infrared spectroscopy equipped with attenuated total reflectance device. From UV-Vis analysis, the resulting exfoliated graphene concentration is 0.154 mg/ml from 0.1 g of activated carbon. The field emission scanning electron microscopy proved that stacking layers of graphene is observed on the exfoliated product.